Assessing Autophagy in Muscle Stem Cells - Campanario, Silvia; Ramírez-Pardo, Ignacio; Hong, Xiaotong; Isern, Joan; Muñoz-Cánoves, Pura (Frontiers in Cell and Developmental Biology, 2021)
Adult skeletal muscle is a stable tissue under normal conditions but has a remarkable ability to regenerate by virtue of its resident stem cells (satellite cells). Satellite cells exist in a quiescent state; however, in response to injury, they enter the cell cycle and proliferate to provide sufficient progeny to form mature myofibers, or return to the quiescent state (self-renewal). Maintenance of satellite cell quiescence, and entry of satellite cells into the activation state requires autophagy, a fundamental degradative and recycling process that preserves cellular proteostasis. With aging, satellite cell regenerative capacity declines, correlating with loss of autophagy. Enhancing autophagy in aged satellite cells restores their regenerative functions, underscoring this proteostatic activity´s relevance for tissue regeneration. Here we describe two strategies for assessing autophagic activity in satellite cells from GFP-LC3 reporter mice, which allows direct autophagosome labeling, or from non-transgenic (wild-type) mice, where autophagosomes can be immunostained. Treatment of GFP-LC3 or WT satellite cells with compounds that interfere with autophagosome-lysosome fusion enables measurement of autophagic activity by flow cytometry and immunofluorescence. Thus, the methods presented permit a relatively rapid assessment of autophagy in stem cells from skeletal muscle in homeostasis and in different pathological scenarios such as regeneration, aging or disease